Health training – preparing an organism for coping with COVID-19 - Gawda, Piotr; Zieliński, Grzegorz; Zawadka, Magdalena; Byś, Aleksandra (Polish Journal of Public Health, 2020)
Coexistence of organisms in the world is a dynamic state, requiring complying with certain rules in order to sustain biological balance. Huge human expansion into the Earth ecosystem results in numerous crises. One of them is a problem of pandemic concerning COVID-19. The dynamics of epidemic development is changing. More and more statistical analyses regarding clinical course of this disease are appearing. Prophylactic actions, specific for each country, are taken aimed at reduction of quantity and intensity of infections in the society in such a way as to make health care systems efficient at the time of pandemic. Great hopes are put in natural defence mechanisms of human body, the effectiveness of which, to a large extent, depends on ourselves. As part of prophylactic actions, heath trainings, that is regular physical exercises together with proper management of rest, nutrition and sleep, can improve physical performance of an organism, strengthen its immunological defence, adapting it to greater burdens. Such a relative load, that impairs functioning of respiratory system and as a consequence limits the ability to obtain energy necessary for independent maintenance of vital functions, may be a clinic course of COVID-19. Development of the Internet and social media considerably facilitates search for those kinds of physical activities that can be performed in the home. That is why, despite the isolation and movement restrictions, everyone can find own way to actively spend free time, which will positively influence his/her organism, and consequently, increase chances in potential encounter with the virus. Health training – preparing an organism for coping with COVID-19.